2022
DOI: 10.3390/agronomy12020424
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Angle of Repose and Coefficient of Rolling Friction for Wood Pellets

Abstract: The determination of the angle of repose for granular materials is indispensable for their handling and the design of containers and technological processing equipment. On the other hand, computational simulations have become an essential tool to understand the micro-behavior of the granular material and to relate it with the macro-behavior. The experimental determination of the angle of repose has a fundamental role when defining the required parameters to perform realistic simulations. However, there is a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Classical theories are suitable for determining these loads under static conditions, with the Janssen formula [1] being the world's most widely used. However, numerical methods began to be applied to silo calculations in the 1970s [2], and since then, they have experienced a great surge, especially during the 21st century, thanks to advances in computing [3][4][5][6][7][8][9][10][11][12]. With these techniques, it is possible to accurately predict dynamic loads occurring during both the filling and the emptying of silos, in addition to modeling the static conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Classical theories are suitable for determining these loads under static conditions, with the Janssen formula [1] being the world's most widely used. However, numerical methods began to be applied to silo calculations in the 1970s [2], and since then, they have experienced a great surge, especially during the 21st century, thanks to advances in computing [3][4][5][6][7][8][9][10][11][12]. With these techniques, it is possible to accurately predict dynamic loads occurring during both the filling and the emptying of silos, in addition to modeling the static conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of the repose angle was carried out to determine the nature of the adhesion or cohesion of the granules, that would affect the flow properties of the granule. Repose angle of 22.07°, showed the excellent flow property [15,16]. This value showed that granule was effortless to flow and will make uniform shape of tablet core.…”
Section: Discussionmentioning
confidence: 89%
“…(2) The angle of repose test is a widely employed method for calibrating discrete elemental model parameters [20][21][22][23]. Nevertheless, its applicability is constrained when dealing with soils characterized by high water content, primarily due to inherent limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The angle of repose test is a common method for calibrating model parameters for discrete elements [20][21][22][23]; However, its applicability is limited in soils with high water content. Consequently, the slump test was chosen for its ability to provide a reliable representation of the soil's cohesion, friction properties, and mobility.…”
Section: Tillage Calibration Testmentioning
confidence: 99%